Syphilis vaccine development: Aligning vaccine design with manufacturing requirements - Sean Waugh; Caroline E. Cameron (Taylor & Francis Group, 2024)
Syphilis, caused by Treponema pallidum subsp. pallidum, is a global health concern with increasing rates worldwide. Current prevention strategies, including screen-and-treat approaches, are not sufficient to resolve rising infection rates, emphasizing the need for a vaccine. Developing a syphilis vaccine necessitates a range of cross-disciplinary considerations, including essential disease-specific protection, technical requirements, economic feasibility, manufacturing constraints, public acceptance, equitable vaccine access, alignment with global public vaccination programs, and identification of essential populations to be vaccinated to achieve herd immunity. Central to syphilis vaccine development is prioritization of global vaccine availability, including access in low- to middle-income settings. Various vaccine platforms, including subunit, virus-like particle (VLP), mRNA, and outer membrane vesicle (OMV) vaccines, present both advantages and challenges. The proactive consideration of both manufacturing feasibility and efficacy throughout the pre-clinical research and development stages is essential for producing an efficacious, inexpensive, and scalable syphilis vaccine to address the growing global health burden caused by this disease.